Design, Meaning, and Intention: Communication in Times of a Pandemic - Costa, Maria Luísa (2022)
In this paper, we assess how communication design has contributed, in the context of the SARS CoV 2 pandemic, to inform and motivate people to AQ1 take safe individual actions, particularly physical distancing and the use of masks. Throughout the study, and in order to assess the communicative effectiveness of images, we contextualize the concepts of poster and image. Thus, we analyze a set of images produced and presented on posters through a descriptive grid and AQ2 an open survey to the community.